An assessment of clients’ performance in having an efficient building process in Uganda - Alinaitwe, Henry Mwanaki (Journal of Civil Engineering and Management, 2008)
Over the years researchers have paid little attention to the performance of the clients in the building industry. Much of the research on improvement of performance of the construction industry has mainly focused on contractors and the supply chain. The performance of a client is important because any decision made will affect project success. Failure on the part of the client might lead to stress factors causing significant problems in successive stages of the project. This research is an investigation into the roles of the client to find out whether clients in the building industry in Uganda are playing their part. Due to the non‐specific nature of clients, a guided questionnaire survey was carried out among architects who normally work with different types of clients. The majority of the building clients in Uganda are individuals followed by limited liability companies. It was found out that delay by clients in paying the contractors is a major factor affecting the performance of contractors. Almost all clients do not support training of the workers in its different forms. Construction works start before the designs are completed and the majority of the variations is due to incomplete briefs and designs. Many clients or their representatives do not attend meetings as regularly as would have been necessary. This study reveals information that will help clients in their future projects for ensuring successful building project implementation. Užsakovo dalyvavimo efektyviame statybos procese įvertinimas Ugandoje Santrauka. Daug metų mokslininkai mažai kreipė dėmesio į užsakovų dalyvavimą statybos pramonėje. Dauguma atliktų mokslinių tyrimų, susijusių su statybos pramonės darbų kokybės gerinimu, yra orientuoti į rangovus ir tiekimo grandinę. Užsakovo dalyvavimas yra svarbus todėl, kad kiekvienas priimtas sprendimas gali daryti įtaką projekto sėkmei. Užsakovų žlugimas gali sudaryti įtampą, kuri gali kliudyti sėkmingai vykdyti projekto stadijas. Straipsnyje buvo nagrinėjamas užsakovų vaidmuo, norint nustatyti, ar užsakovai Ugandoje aktyviai dalyvauja statybos pramonėje. Buvo atlikta apklausa architektų, kurie dirba su įvairiais užsakovais. Dauguma statybos užsakovų Ugandoje yra ribotos atsakomybės įmonės. Taip pat buvo pastebėta, kad užsakovo delsimas sumokėti rangovams yra vienas iš svarbiausių veiksnių, darančių įtaką rangovų darbui. Beveik visi užsakovai nepritaria darbuotojų kvalifikacijos tobulinimui įvairiais būdais. Dažniausiai statybos darbai yra pradedami dar nebaigus projektavimo darbų ir dauguma nukrypimų yra dėl neparengtos techninės dokumentacijos. Dauguma užsakovų ar jų atstovų nereguliariai dalyvauja svarbiuose susitikimuose. Šis tyrimas pateikia informaciją, kuri padės užsakovams ateities projektuose ir užtikrins sėkmingą statybos projektų vykdymą. Reikšminiai žodžiai: vaidmuo, užsakovai, statyba, produktyvumas, dalyvavimas, Uganda. First Published Online: 14 Oct 2010